Penerapan Prinsip Transparansi Dalam Pengelolaan Alokasi Dana Desa (ADD) Di Desa Jaya Makmur Kecamatan Binongko Kabupaten Wakatobi - Lili, La; Rahman, Rahman; Jopang, Jopang (Universitas Halu Oleo, 2021)
This study aims to determine the application of the principle of transparency in the management of Village Fund Alocation (ADD) in Jaya Makmur Village, Binongko District Wakatobi Regency. This type of research is qualitative research. The date collection techniques used consisted of interviews and documentation. The resource person used in this study were village officials and the hamlet head of Jaya Makmur village. The result ot this study indicate that the management of Village Fund Allocation in Jaya Makmur Village is transparent. Based on the transparency indicator, it shows that there is availability that can be accesed by the public through APBDes billboards, clarity and completeness of information by involving the community in the implementation of development, there is an open process by involving the community in the planning, deliberation and implementation processes, as well as the regulatory framework which guarantees transparency, namely Permendagri Number 113 of 2014 concerning Village Financial Management.